2018
DOI: 10.1186/s12967-018-1580-x
|View full text |Cite
|
Sign up to set email alerts
|

Resibufogenin suppresses colorectal cancer growth and metastasis through RIP3-mediated necroptosis

Abstract: BackgroundNecroptotic susceptibility is probably an intrinsic weakness of cancer. Here, we report that resibufogenin, a member of bufadienolide family, suppresses the growth and metastasis of colorectal cancer (CRC) through induction of necroptosis in vivo.MethodsSW480 cells with stably expressing enhanced green fluorescence protein were xenografted to BALB/c-nu mice to observe the growth of tumors. Liver metastasis was observed by injection of MC38 cells beneath the splenic capsule of mice. Protein expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 33 publications
(42 reference statements)
1
70
0
1
Order By: Relevance
“…It has been shown to exhibit anti-proliferative effects in multiple cancer cells [142144]. Recently, Han et al [110] have reported that resibufogenin was shown to suppress the growth and metastasis of colorectal cancer by inducing RIPK3 necroptosis both in vitro and in vivo through upregulating RIPK3 and MLKL protein at Ser358. The study also demonstrated that resibufogenin may activate three key metabolic enzymes, including glycogen phosphorylase (PYGL), glutamine synthetase (GLUL), and glutamate dehydrogenase (GLUDl) in a RIPK3 dependent manner, and resibufogenin was also found to suppress liver metastasis of colorectal cancer in mouse models [110].…”
Section: Natural Compoundsmentioning
confidence: 99%
“…It has been shown to exhibit anti-proliferative effects in multiple cancer cells [142144]. Recently, Han et al [110] have reported that resibufogenin was shown to suppress the growth and metastasis of colorectal cancer by inducing RIPK3 necroptosis both in vitro and in vivo through upregulating RIPK3 and MLKL protein at Ser358. The study also demonstrated that resibufogenin may activate three key metabolic enzymes, including glycogen phosphorylase (PYGL), glutamine synthetase (GLUL), and glutamate dehydrogenase (GLUDl) in a RIPK3 dependent manner, and resibufogenin was also found to suppress liver metastasis of colorectal cancer in mouse models [110].…”
Section: Natural Compoundsmentioning
confidence: 99%
“…A recent study also showed that resibufogenin suppresses growth and metastasis of CRC through RIPK3-mediated necroptosis. This kind of effect can be reduced by RIPK3 deficiency rather than the use of z-VAD, a pan-caspase general inhibitor, which confirms the role of necroptosis in the treatment of CRC[ 36 ].…”
Section: Necroptosis and Crcmentioning
confidence: 74%
“…Han et al suggested that it can initiate necroptosis to suppress metastasis in both human CRC HCT116 and SW480 cells and in an in vivo xenograft mouse model through the elevation of RIP3. In addition, it also promotes the expression of PYGL, GLUD1 and GLUL, which are important enzymes, via RIP3 to generate ROS [120].…”
Section: Treatments Targeting Both Ros and Necroptosismentioning
confidence: 99%